A Conspectus of Early Cilician Pottery - Garstang, J.
Mersin: Neolithic Period, Chalcolithic Period, Early or Proto-Chalcolithic Period, Middle Chalcolithic Period (ca. 3500 B. C.), Late Chalcolithic Period (ca. 3300-3100 B. C.) — Tarsus: Period of Ceramic Forms Common to a Large Area of Anatolian Culture, Period of the Dark-on-Light Painted Pottery with Near Eastern, Especially Syrian, Affiliations, Period of Pottery Similar to That of Older Phases of the Hittite Empire, Period of the New Hittite Empire — Chronology.